2012
DOI: 10.1055/s-0032-1324727
|View full text |Cite
|
Sign up to set email alerts
|

DSD Due to 5α-Reductase 2 Deficiency - from Diagnosis to Long Term Outcome

Abstract: Most of the patients with 5α-RD 2 deficiency are reared in the female social sex due to their severely undervirilized external genitalia but ~60% who have not been submitted to orchiectomy in childhood undergo male social sex change at puberty. In our cohort of 30 cases from 18 families, all subjects were registered in the female social sex except for two children-one who had an affected uncle and the other who was diagnosed before being registered. The majority of the patients were satisfied with the long-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(7 citation statements)
references
References 47 publications
1
5
0
1
Order By: Relevance
“…Our study confirms prepubertal presentation in approximately half of the SRD5A2 deficiency patients, (6,23,24), inaccuracy of T/DHT ratio and female to male gender change in half of the patients with initial female sex assignment (48-50%) (3,25). The latter observation suggests that gender role change is not universal in SRD5A2 deficiency patients with initial female sex assignment (23,26).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our study confirms prepubertal presentation in approximately half of the SRD5A2 deficiency patients, (6,23,24), inaccuracy of T/DHT ratio and female to male gender change in half of the patients with initial female sex assignment (48-50%) (3,25). The latter observation suggests that gender role change is not universal in SRD5A2 deficiency patients with initial female sex assignment (23,26).…”
Section: Discussionsupporting
confidence: 82%
“…Inaccurate results are not uncommon with basal or human chorionic gonadotropin (hCG)-stimulated total testosterone (T) to dihydrotestosterone (DHT) ratio, the commonly used tests for diagnosis of SRD5A2 deficiency (3). Urinary steroid profiling (ratio of 5α to 5β steroid metabolites), a more reliable biochemical test, is a less available and laborious test with limited diagnostic accuracy in younger infants (< 3 months of age) (4).…”
Section: Introductionmentioning
confidence: 99%
“…Men with XY DSD conditions are reported to be more satisfied after surgical corrections of genitals, although repeated surgical procedures and complications may have a negative impact on sexual function (Callens et al, 2015;Callens et al, 2013). In a study on persons with 5a-RD2 deficiency, penile length was not associated with satisfaction of sexual activity (Costa, Domenice, Sircili, Inacio, & Mendonca, 2012). In men with PAIS, sexual function was reported to be seriously impaired (Bouvattier et al, 2006).…”
Section: Satisfaction With Genitals and Genital Functionmentioning
confidence: 99%
“…With a thorough understanding of anticipated events at puberty, an initial male sex assignment should be considered. Long-term follow up has shown that many affected individuals who live as male are participating in long-term, heterosexual relationships (37). If fertility is desired, most of these couples will require assisted methods of reproduction (38).…”
Section: Managementmentioning
confidence: 99%